2007
DOI: 10.1089/jop.2006.0097
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Topical Olopatadine And Epinastine in The Botulinum Toxin B—Induced Mouse Model of Dry Eye

Abstract: Topical olopatadine and epinastine do not cause significantly additional damage to the compromised ocular surface secondary to dry eye after continuous 4-week, twice-daily application. Topical olopatadine and epinastine appear to have comparable effects on aqueous tear-production and corneal-surface changes in this mouse model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The finding in Wisconsin [41] showed that dry eye could be related to the use of antihistamines that have anticholinergic properties owing to high muscarinic receptor binding. Systemic antihistamines, including old and newer generations, have been shown to potentially cause clinically meaningful damage to the ocular surface as a result of anti-muscarinic activity on the M3 receptors that results in a decrease in both aqueous and mucin tear [42]. There is no consensus of opinion about the effect of estrogen on DED.…”
Section: Discussionmentioning
confidence: 99%
“…The finding in Wisconsin [41] showed that dry eye could be related to the use of antihistamines that have anticholinergic properties owing to high muscarinic receptor binding. Systemic antihistamines, including old and newer generations, have been shown to potentially cause clinically meaningful damage to the ocular surface as a result of anti-muscarinic activity on the M3 receptors that results in a decrease in both aqueous and mucin tear [42]. There is no consensus of opinion about the effect of estrogen on DED.…”
Section: Discussionmentioning
confidence: 99%
“…Tranilast, which is the active ingredient in Tramelas PF, has an inhibitory effect on cell proliferation 12 . Clinical and experimental studies have indicated that olopatadine, which is in Patanol, results in mild ocular surface damage 13,14 .…”
Section: Figmentioning
confidence: 99%
“…To the authors’ knowledge, the effect of topical antihistamines on tear production in dogs has not been evaluated. In mice with botulinum toxin B‐induced dry eye, topical olopatadine and epinastine did not have a significant effect on aqueous tear production 29 . Another study evaluating mice showed olopatadine but not epinastine to cause a significant decrease in tear volume 30 .…”
Section: Discussionmentioning
confidence: 98%